Perancangan Sistem Pengelolaan Keuangan Komite Menggunakan Web Engineering (Studi Kasus : SMK Negeri 1 Gedong Tataan) - setiawansyah setiawansyah; Heni Sulistiani; Ari Sulistiyawati; Arsi Hajizah (Komputika : Jurnal Sistem Komputer, 2021)
Financial management in schools is one of the most important activities, because every activity carried out in school requires financial management. Information systems regarding the recording and processing of committee financial administration data in schools such as recording receipts and disbursements of funds originating from student committee tuition payments into a database to automate the making of the reports needed, so that the finance department will have no difficulty finding student data have not paid school committee fees, it also makes it easier to produce reports on the financial administration of committee fees at the school. The stages in web engineering are Customer communication, Planning, Modeling, Construction in the school committee financial management system application. The results of testing the school committee's financial management information system using the web method engineering at SMK Negeri 1 Gedong Tataan using a web-based application made with the PHP programming language and CodeIgniter framework and MySql database for testing system functionality using blackbox testing to get a value of 100% according to system functionality, and the results of the Web Quality 4.0 test got a score of 87.6% having Very Good criteria from usability testing